Pengaruh Social Media Marketing dan Content Quality terhadap Brand Awareness pada Pengguna Instagram - Jacklin Claudia Culivan; Adryan Rachman (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The rapid growth of digital platforms has driven companies to leverage Instagram as a strategic marketing channel for building Brand Awareness (BA) in an increasingly competitive landscape. This study examines the effect of Social Media Marketing (SMM) and Content Quality (CQ) on BA among Instagram users, both partially and simultaneously. Grounded in Marketing 4.0 theory (Kotler, 2016) and brand awareness constructs (Keller, 2013), SMM is measured through six indicators including posting consistency and Instagram feature utilization, while CQ is assessed through visual appeal, content relevance, and informational value. A quantitative survey method was employed, involving 230 active Instagram users selected through purposive sampling. Data were collected via a Likert-scale (1–5) online questionnaire and analyzed using IBM SPSS Statistics 27 through validity, reliability, classical assumption tests, and multiple linear regression. Simultaneous testing revealed that SMM and CQ significantly affect BA (F = 178.215; sig. <0.001). Partially, SMM shows no significant effect on BA (β = 0.028; sig. = 0.603), while CQ demonstrates a positive and significant effect (β = 0.825; sig. <0.001) as the dominant variable. The R² value of 0.617 indicates that 61.7% of BA variation is explained by both variables. These findings establish content quality as the primary determinant of brand awareness on Instagram, and brands are advised to prioritize creative, relevant, and informative content strategies.